Randomized Trial on Echocardiography-Guided Ductus Arteriosus Treatment to Reduce Necrotizing Enterocolitis - Bravo, María Carmen; Sánchez-Salmador, Rebeca; Moral-Pumarega, María Teresa; López-Azorín, Manuela; Mosqueda-Peña, Rocío; Dorronsoro, Izaskun; Cabañas, Fernando; Pellicer, Adelina (Frontiers in Pediatrics, 2022)
Objective. Patent ductus arteriosus (PDA) approach remains controversial. We aim to evaluate whether echocardiography-guided (EchoG) PDA closure (to reduce drug exposure) and 24h-continuous ibuprofen infusion (24h-IB) (to reduce peak concentration), compared to EchoG PDA closure plus conventional bolus (bolus-IB), reduces severe bowel adverse event rate in preterm infants with hemodynamically significant (hs) PDA. Study Design: Multicenter, blinded, randomised controlled trial. Infants with <28 weeks’ gestation underwent routine echocardiographic assessment (18-72h of birth); infants with 28-33 weeks were screened only in case that PDA was clinically suspected. HsPDA was considered if ductal diameter >1.5 mm and indicators of pulmonary overflow, systemic hypoperfusion, or both were present. Pharmacodynamics effect of CYP450 genotypes was also analised. Results. One hundred forty six infants (median gestational age 26 [25-28] weeks; median birth weight 881 [704-1100] g) were randomised to 24h-IB (n=70) or bolus-IB (n=76) study group at 86 (58-140) h from birth. Groups were comparable regarding perinatal and neonatal clinical data but higher prevalence of male sex in the bolus-IB group was found. Neither severe bowel adverse event rate [10% (24h-IB) and 2.6% (bolus-IB), p=0.1] nor ductal closure rate were different between the study groups. Postnatal age and peripheral SaO2 at treatment start, and pulmonary hemorrhage were associated to severe bowel events, independently of treatment group allocation. CYP2C8 genetic polymorphisms was associated with ibuprofen efficacy (p=0.03). Conclusions. Ibuprofen intravenous continuous infusion compared to bolus infusion in preterm infants with hsPDA shows similar rates of success and does not reduce the prevalence of severe bowel events.